Privatization by Auction: Determinants of Asset Prices in Kosovo. Issue 4 (3rd July 2020) - Gashi, Petrit; Hashi, Iraj; Pugh, Geoff
ABSTRACT: The contribution of this paper is twofold. First, we use the administrative dataset of the Privatization Agency of Kosovo between 2003 and 2018 to analyze the factors affecting privatization prices. We identify the effects of five sets of variables: features of the auction process; Privatization Agency-related variables; buyer characteristics; asset characteristics; and election-related variables. Second, beyond this econometric investigation, we explore the complexities of the privatization process in Kosovo, in particular the Kosovo-specific factors that may have influenced the prices of privatized enterprises and assets. Policy implications suggest measures to enhance the credibility of the privatization process and related institutions.